2X-6=3X+7

Simple and best practice solution for 2X-6=3X+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2X-6=3X+7 equation:


Simplifying
2X + -6 = 3X + 7

Reorder the terms:
-6 + 2X = 3X + 7

Reorder the terms:
-6 + 2X = 7 + 3X

Solving
-6 + 2X = 7 + 3X

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-3X' to each side of the equation.
-6 + 2X + -3X = 7 + 3X + -3X

Combine like terms: 2X + -3X = -1X
-6 + -1X = 7 + 3X + -3X

Combine like terms: 3X + -3X = 0
-6 + -1X = 7 + 0
-6 + -1X = 7

Add '6' to each side of the equation.
-6 + 6 + -1X = 7 + 6

Combine like terms: -6 + 6 = 0
0 + -1X = 7 + 6
-1X = 7 + 6

Combine like terms: 7 + 6 = 13
-1X = 13

Divide each side by '-1'.
X = -13

Simplifying
X = -13

See similar equations:

| x=150+0.85(x) | | w-147.67=144.67 | | 3/5x21=3x | | .3333p+7=12-.6666p | | (2x^2)/(0.8-x^2)=53.3 | | 3/5+3=21x | | z/325=7 | | z/23=6 | | 1/9p=5/6 | | x=200+0.8(x) | | -5(X-4)+8X=6X-2 | | -6y-9=-3(y+9) | | x+65=50+75 | | 10/27=5/9t | | z^23=6 | | 18y-6=8y-70 | | 50+75=x+65 | | 5(X+4)/6=2X-5 | | 0.2x+1-2=0.5 | | x+(.01x)=15000 | | D=7/3(m-76) | | 2x/2-3x-1=0 | | 5x-3/2+6=-11 | | x-(0.01*x)=1500 | | -7-35/8 | | -6+x-8=24 | | x-(0.1*x)=1500 | | x^2-6x+12=8 | | 8(X-8)=7(X-8) | | 25=-5+x-7 | | 11-9x-7-3x=7 | | 81/3=5/2c |

Equations solver categories